ANALISIS RETROSPEKTIF STRATEGI LOKASI DAN TATA LETAK WARUNG KELONTONG ‘ASA’: BUKTI EMPIRIS DAMPAK PERUBAHAN LINGKUNGAN TERHADAP KEBERLANGSUNGAN USAHA - Chalawah Ummy Sa'diyah; Guntur Setiawan (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2026)
Not all small businesses are able to remain sustainable even when offering similar products, prices, and marketing strategies, as external conditions particularly the surrounding environment and spatial layout often play a decisive role in performance. This study examines the evolution of the “ASA” Convenience Store from 2009 to 2020, which initially grew due to its strategic proximity to a college campus, student housing, and a morning market, but experienced a sharp decline in customer traffic following the closure of the campus. Using a descriptive-analytical method and a qualitative approach, data were collected through interviews, observations, and historical documentation, and analyzed with reference to Central Place Theory (Christaller, 1933)  and small business layout principles. The findings indicate that while strategic location and effective spatial planning can enhance customer appeal and operational efficiency, these advantages are dynamic and must be continually adjusted to changing socioeconomic conditions, underscoring the importance of adaptive strategies for sustaining small business continuity.